2011
DOI: 10.1165/rcmb.2009-0315oc
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 Family Member 9 Stimulates Chemokine Production and Neutrophil Influx in Mouse Lungs

Abstract: Interleukin-1 (IL-1) is a proinflammatory cytokine that signals through the Type I IL-1 receptor (IL-1RI). Novel IL-1-like cytokines were recently identified. Their functions in lung disease remain unclear. Interleukin-1 family member-9 (IL-1F9) is one such IL-1-like cytokine, expressed in the lungs of humans and mice. IL-1F9 signals through IL-1 receptor-related protein 2 (IL-1Rrp2/IL-1RL2), which is distinct from IL-1RI. We sought to determine if IL-1F9 acts as a proinflammatory cytokine in lung disease. IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
105
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(117 citation statements)
references
References 44 publications
(50 reference statements)
11
105
0
1
Order By: Relevance
“…and CCL20, and cytokines IL-6, G-CSF, and GM-CSF, which can recruit and activate DC, macrophages, neutrophils, T cells, and NK cells. Studies in other epithelial tissues, such as human bronchial epithelial cells and mouse lungs, showed that IL-36, particularly IL-36g, induces the neutrophil-attracting chemokines IL-8 and CXCL1, the T cell-attracting chemokines CXCL10, and the DC-attracting and Th17-attracting chemokine CCL20, as well as cytokines and growth factors, including IL-6, G-CSF, and GM-CSF (35,36). Data from previous studies combined with our data indicate that IL-36g would activate epithelial cells to induce chemokines and recruit inflammatory cells for the initial stages of innate immunity in skin inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…and CCL20, and cytokines IL-6, G-CSF, and GM-CSF, which can recruit and activate DC, macrophages, neutrophils, T cells, and NK cells. Studies in other epithelial tissues, such as human bronchial epithelial cells and mouse lungs, showed that IL-36, particularly IL-36g, induces the neutrophil-attracting chemokines IL-8 and CXCL1, the T cell-attracting chemokines CXCL10, and the DC-attracting and Th17-attracting chemokine CCL20, as well as cytokines and growth factors, including IL-6, G-CSF, and GM-CSF (35,36). Data from previous studies combined with our data indicate that IL-36g would activate epithelial cells to induce chemokines and recruit inflammatory cells for the initial stages of innate immunity in skin inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…DNA-binding activity assays for 40 TFs in nuclear proteins were determined using Panomics Procarta Transcription Factor Assay Kit (40-plex Panel 1; Affymetrix, Santa Clara, CA) based on Luminex xMAP technology as previous study (Jiang et al 2006;Ramadas et al 2011). Briefly, nuclear protein was incubated with a mixture of biotin-labeled cis-element probes to form protein/DNA complexes.…”
Section: Methodsmentioning
confidence: 99%
“…These ligands included double-stranded RNA [poly(I:C)], flagellin, and Mycoplasma fermentans synthetic lipopeptide (FSL-1), LPS, and zymosan and implicate the IL-36s in immunity against bacteria, fungi, and viruses (24,79,82). Confirmatory and complementary studies using intact microorganisms have reported increased production of IL-36g in the lung and oral epithelial cells after exposure to rhinovirus, dust mites, or the bacterial pathogens Pseudomonas aeruginosa or Porphyromonas gingivalis (22,(83)(84)(85), in monocytes activated by LPS (86), and in macrophages infected with Mycobacterium tuberculosis (87). All three IL-36s can be induced in peripheral blood mononuclear cells by the opportunistic fungal pathogen Aspergillus fumigatus (88), whereas LPS and Burkholderia species of bacteria have been reported to increase the production of IL-36a in macrophages (89,90).…”
Section: Gsdmd-ntmentioning
confidence: 99%
“…It is conceivable that IL-33 can act in a similar manner. Although it remains to be determined whether the IL-36s are proteolytically processed in vivo, the likelihood that they can act as full-length proteins (20)(21)(22)(23)(24)78) or may be activated by proteases other than caspase-1 (73,75,76) opens the possibility that the IL-36s are not affected by the viral immune evasion mechanisms that block the activation of the inflammasome (Fig. 4).…”
Section: Viral Immune Evasion and Potential Counteraction By Il-36mentioning
confidence: 99%
See 1 more Smart Citation